The importance of placebo effects in enhancing palliative care interventions. Issue 2 (21st January 2014) - Lucas, V; Booth, S
Abstract : In this narrative review, we examine evidence that may help to explain how placebo effects contribute to the effectiveness of palliative care interventions for the relief of symptoms such as pain, breathlessness and depression, and how they may underlie the impact of complementary therapies. We discuss the different ways of conceptualising placebo phenomena, including the importance of the therapeutic relationship, the context of care and the significance of meaning. There is increasing evidence from neuroscience that the term 'placebo effect' describes a number of phenomena that may explain the effectiveness of therapeutic interventions that affect the perception of symptoms. A greater appreciation of placebo effects emphasises the importance of addressing social, psychological, and spiritual factors with equal rigour. Commissioning bodies, rightly concerned about the evidence base for clinical interventions, need to recognise the multifaceted nature of symptom control measures and to realise that the focus for palliative care research needs to be on the specialty as a complex integrated intervention rather than on a series of individually evaluated measures.